Effectiveness of Ordinance No. 2501 in Protecting Women from Sexual Harassment in Quezon City - Ramces Dili; Roi Jones Abellana; Xander De Jesus; Christian Joriz Martinez; Renier Pasiona (Mengeja Indonesia Publisher, 2022)
This study sought the effectiveness of City Ordinance No. 2501, otherwise known as the Gender and Development (GAD) Code of Quezon City, towards its protection of women against sexual harassment. This study sought the programs and projects of the said Local Government Unit (LGU) and how the residents and victims of sexual harassment in Quezon City view its effectiveness. Moreover, it sought out the mechanisms for its implementation. This study followed a mixed methodology with qualitative data from interviews, data analysis, and quantitative data from surveys. Such methodology was a means to procure a holistic goal of creating recommendations. This study concluded that the programs and projects for GAD and sexual harassment are aligned with City Ordinance No. 2501. Present in its implementation are mechanisms for reporting sexual harassment cases and ways to aid the victim. While the present of such exists, the victims of sexual harassment and residents within Quezon City do not strongly agree with the ordinance being ‘effective’ as they do not feel safety, inclusivity, and comfortability. This was mostly due to economic and social circumstances. Hence, this study recommend that it improves its dynamicity and reachability for stronger implementation, consideration for inclusivity, and better information dissemination regarding the ordinance.